Uptake of 13-Valent Pneumococcal Conjugate Vaccine among US Adults Aged 19 to 64 Years with Immunocompromising Conditions. Issue 1 (2nd January 2020) - Vietri, Jeffrey; Harnett, James; Emir, Birol; Chilson, Erica
ABSTRACT: The CDC Advisory Committee on Immunization Practices (ACIP) recommended immunization with the recently licensed 13-valent pneumococcal conjugate vaccine (PCV13) for high-risk (immunocompromised) adults aged ≥19 years in 2012. This was in addition to the 23-valent pneumococcal polysaccharide vaccine (PPSV23). Data on vaccine-specific uptake among these individuals were previously unavailable. This retrospective observational study analyzed PCV13 uptake in immunocompromised patients aged 19–64 years. Data were acquired from insurance claims (N = 267, 022) and electronic health records (EHR; N = 572, 055) from October 2011–October 2016. Descriptive statistics were provided. Demographics were similar across the two database cohorts: mean age 49.7–51.0 years, 57–62% female, and >70% white. Iatrogenic immunosuppression was the most common high-risk category (33.3–44.2%). PCV13 uptake was 7.3% (95% CI: 7.25–7.45) in insurance claims and 9.9% (95% CI: 9.80–9.96) in EHR. Patients with HIV had the highest rate of PCV13 uptake; patients with multiple risk factors were above the mean in both cohorts. A Kaplan-Meier analysis was conducted to include patients lost to follow-up, with 441, 657 and 722, 071 patients for insurance claims and EHR, respectively. PCV13 uptake was only slightly higher: 9.3% (95% CI: 9.14–9.47) and 13.1% (95% CI: 12.93–13.19) for insurance claims and EHR, respectively. Four years after the ACIP 2012 recommendation, PCV13 uptake in high-risk adults aged19–64 years was low at <15% in all overall analyses. Clinicians caring for these patients should ensure adherence to the ACIP recommendation to minimize the risk of pneumococcal disease.